MR-guided radiotherapy in rectal cancer: First clinical experience of an innovative technology. (September 2019) - Chiloiro, Giuditta; Boldrini, Luca; Meldolesi, Elisa; Re, Alessia; Cellini, Francesco; Cusumano, Davide; Corvari, Barbara; Mantini, Giovanna; Balducci, Mario; Valentini, Vincenzo; Gambacorta, Maria Antonietta
Highlights: This study represents one of the first reports of online MRgRT. Integrated Low-field MR provides better anatomical visualization than CBCT or MVCT. Better visualization of the target can help to reduce the margins from CTV to PTV. MRgRT appears a feasible option in rectal cancer treatment offering potential benefits. MRgRT represents a promising technology for rectal cancer management.